Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/cam4.5633
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of GI‐NECs involving three main signaling pathways

Abstract: Background Gastrointestinal (GI)‐neuroendocrine neoplasms (NENs) are subclassified in neuroendocrine tumors (NETs), neuroendocrine carcinomas (NECs), and mixed neuroendocrine–non‐neuroendocrine neoplasms (MiNENs). The genetic characteristics of GI‐NEN has been a hot issue in recent years, but more studies are needed to provide further details. This study aims to provide additional data about genomic characteristics of GI‐NENs and the genetic differences between NETs and NECs. Patients and Methods Thirteen samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…However 4 of Grade 2 NETs showed null pattern of p53 in our study. Qiong Dai et al in their study of molecular alteration in GI NENs, also found mutated pattern / Null pattern of p53 in two of G2 NETs [12]. Disease free survival among patients of Grade 2 NET with null pattern and grade 3 tumors with null pattern in our study were comparable (42 month and 32 months respectively), though one patient grade 2 NET had a higher overall survival of 114 months with disease and died of disease.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…However 4 of Grade 2 NETs showed null pattern of p53 in our study. Qiong Dai et al in their study of molecular alteration in GI NENs, also found mutated pattern / Null pattern of p53 in two of G2 NETs [12]. Disease free survival among patients of Grade 2 NET with null pattern and grade 3 tumors with null pattern in our study were comparable (42 month and 32 months respectively), though one patient grade 2 NET had a higher overall survival of 114 months with disease and died of disease.…”
Section: Discussionsupporting
confidence: 67%
“…Null pattern/ mutated pattern in grade 2 NET could represent transformation of grade 2 NET to higher grade and poor survival [13]. Qiong Dai et al commented that null pattern IHC expression of p53 cannot be used to reliably distinguish NETs and NEC [12]. Like our study Qiong Dai et al found a signi cant difference in expression of p53 between NET( G2 NET, G3NET) and NEC [12].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations